Severe manifestations in carrier females in X linked retinitis pigmentosa. Issue 10 (October 1997) - Souied, E; Segues, B; Ghazi, I; Rozet, J M; Chatelin, S; Gerber, S; Perrault, I; Michel-Awad, A; Briard, M L; Plessis, G; Dufier, J L; Munnich, A; et al.
Abstract : Retinitis pigmentosa (RP) is a group of progressive hereditary disorders of the retina in which various modes of inheritance have been described. Here, we report on X linked RP in nine families with constant and severe expression in carrier females. In our series, however, the phenotype was milder and delayed in carrier females compared to hemizygous males. This form of X linked RP could be regarded therefore as partially dominant. The disease gene maps to chromosome Xp2.1 in the genetic interval encompassing the RP3 locus (Zmax=13.71 at the DXS1100 locus). Single strand conformation polymorphism and direct sequence analysis of the retinitis pigmentosa GTPase regulator (RPGR) gene, which accounts for RP3, failed to detect any mutation in our families. Future advances in the identification of X linked RP genes will hopefully help to elucidate the molecular basis of this X linked dominant RP.